THE VALLEY OF PALACES AND GARDENS AS AN EXAMPLE OF COOPERATION AT TOURISM MARKET - Rapacz, Andrzej; Gryszel, Piotr; Jaremen, Daria (Acta Scientiarum Polonorum. Oeconomia, 2010)
Contemporary tourism market undergoes ongoing improvements by new, interesting tourism products. However, in order to create them it becomes indispensable for many entities, organizations and institutions to enter into mutual cooperation. Among such entities there are not only entrepreneurs, but also territorial self-government units, social organizations, as well as scientific and research institutions. Their cooperation may result in finding a client for the prepared tourism offer. Having also considered extensive competition in the region and between regions one has to conclude that the most desirable type of cooperation in tourism is the one taking the form of a tourism cluster. Growing interest in problems of regional innovation systems and the concept of a cluster justifies the question about usefulness of the latter also in tourism. The objective of the hereby study is to point to advantages and disadvantages of the concept, or rather coopetition taking the form of a cluster at tourism market. The article discusses the concept of such tourism cluster for the Karkonosze Mountains and Jelenia Góra region.